PI3K/AKT inhibition induces caspase-dependent apoptosis in HTLV-1 transformed cells - Jeong, Soo-Jin (2007)
The phosphatidylinositol-3-kinase (PI3K) and AKT (Protein Kinase B) signaling pathways play an important role in regulating cell cycle progression and cell survival. In previous studies, we demonstrated that AKT is activated in HTLV-1 transformed cells and that Tax activation of AKT is linked to p53 inhibition and cell survival. In the present study, we extend these observations to identify regulatory pathways affected by AKT in HTLV-1-transformed cells. We demonstrate that inhibition of AKT reduces the level of phosphorylated Bad, an important member of the pro-apoptotic family of proteins. Consistent with the decrease of phosphorylated Bad, cytochrome c is released from the mitochondria and caspase 9 is activated. Pre-treatment of the cells with caspase-9 specific inhibitor z-LEHD-FMK or pan caspase inhibitor Ac-DEVD-CHO prevented LY294002-induced apoptosis. Of interest, p53 siRNA prevents LY294002-induced apoptosis in HTLV-1-transformed cells, suggesting that p53 reactivation is linked to apoptosis. In conclusion, the AKT pathway is involved in targeting multiple proteins which regulate caspase- and p53-dependent apoptosis in HTLV-1-transformed cells. Since AKT inhibitors simultaneously inhibit NF-κB and activate p53, these drugs should be promising candidates for HTLV-1-associated cancer therapy.